Credibility of native and non-native speakers of English revisited: Do non-native listeners feel the same? - Hanzlíková, Dagmar; Skarnitzl, Radek (Research in Language, 2017)
This study reports on research stimulated by Lev-Ari and Keysar (2010) who showed that native listeners find statements delivered by foreign-accented speakers to be less true than those read by native speakers. Our objective was to replicate the study with non-native listeners to see whether this effect is also relevant in international communication contexts. The same set of statements from the original study was recorded by 6 native and 6 non-native speakers of English. 121 non-native listeners rated the truthfulness of the statements on a 7-point scale. The results of our study tentatively do confirm a negative bias against non-native speakers as perceived by non-native listeners, showing that subconscious attitudes to language varieties are also relevant in communication among non-native speakers.